THE PREDICTION OF THE THERMOHYDROGRAVIDYNAMIC THEORY CONCERNING THE STRONGEST INTENSIFICATIONS OF THE SEISMOTECTONIC AND CLIMATIC PROCESSES IN CALIFORNIA SINCE 9 AUGUST, 2017 AND BEFORE 3 MARCH, 2018 - Simonenko, Sergey V. (International Journal of Research -GRANTHAALAYAH, 2017)
The article presents (on October 12, 2017) the prediction (made on 9 August, 2017) of the established global prediction thermohydrogravidynamic principle (of the developed thermohydrogravidynamic theory based on the author’s generalization of the first law of thermodynamics for non-stationary cosmic gravitation) concerning the strongest intensifications of the seismotectonic and climatic processes in California (since 9 August, 2017 and before 3 March, 2018) determined by the maximal (near 7 November, 2017) combined integral energy gravitational influence on the internal rigid core of the Earth (and on the Earth as a whole) of the planets (Mercury, Venus, Mars and Jupiter) and the Sun due to the gravitational interactions of the Sun with Jupiter Saturn, Uranus and Neptune. The prediction is based on the established global prediction thermohydrogravidynamic principle (used for the considered real planetary configurations of the Earth and the planets of the Solar System during the range 2004 - 2017) and on the statistical analysis of the previous strongest (according to the U.S. Geological Survey) earthquakes occurred in California near the calculated dates of the local maximal combined planetary and solar integral energy gravitational influences (during the range 2004 2016) on the internal rigid core of the Earth.